To share or not to share? Image data sharing in the social sciences and humanities - Late, Elina; Skov, Mette; Kumpulainen, Sanna (Information research, 2024)
Introduction. The paper aims to investigate image data sharing within social science and humanities. While data sharing is encouraged as a part of the open science movement, little is known about the approaches and factors influencing the sharing of image data. This information is evident as the use of image data in these fields of research is increasing, and data sharing is context dependent. Method. The study analyses qualitative semi-structured interviews with 14 scholars who incorporate digital images as a core component of their research data. Analysis. Content analysis is conducted to gather information about scholars’ image data sharing and motivating and impeding factors related to it. Results. The findings show that image data sharing is not an established research practice, and when it happens it is mostly done via informal means by sharing data through personal contacts. Supporting the scientific community, the open science agenda and fulfilling research funders’ requirements motivate scholars to share their data. Impeding factors relate to the qualities of data, ownership of data, data stewardship, and research integrity. Conclusion. Advancing image data sharing requires the development of research infrastructures and providing support and guidelines. Better understanding of the scholars’ image data practices is also needed.